Factors associated with sexual abuse in children attended at the La Huayrona Commissioner of San Juan de Lurigancho, 2017 - Rea Abad, Olga (2017)
Objective: To determine the factors associated with sexual abuse in children assisted at the Huayrona Police Station in San Juan de Lurigancho, 2017. Materials and Methods: The study was quantitative, retrospective, descriptive level, non-experimental-transversal design. The sample consisted of 30 parents of the children of victims to whom informed consent was previously applied. Results: It is evident that, in the family factor, of the total number of parents, 40% are separated spouses, while 46.7% of cases are committed by a family member. Socioeconomic factor: 80% of spouses work, 46.6% have a low economic income (S/ 300.00 - 600.00 soles). Cultural factor shows that 80% of mothers make decisions at home due to the father's absence. 46.7% of mothers in the home are victims of physical violence Conclusions: Regarding the family factor, most spouses are separated, children are left in the care of close family members, the majority of parent’s work, and their income is low. S/ 300.00 to 600.00 soles. Regarding the cultural factor associated with sexual abuse in most cases who makes decisions at home is the mother since there is absence of the father due to family violence.